THE EFFECT OF CUSTOMER EXPERIENCE MANAGEMENT ON BRAND LOYALTY IN DIGITAL RETAILING - Haryaman, Adang (KRIEZ ACADEMY : Journal of development and community service, 2025)
Background: The rise of digital retailing has revolutionized the way businesses interact with consumers, making customer experience management (CEM) an essential component of success in this competitive landscape. As digital platforms continue to evolve, understanding the factors that influence customer satisfaction and brand loyalty has become crucial for businesses seeking to maintain a loyal customer base. Personalization, ease of use, and customer support are among the key elements that shape the overall customer experience in digital retailing. This study explores the impact of these factors on brand loyalty, providing insights into how businesses can enhance their customer experience strategies to foster long-term relationships with their customers. Aims: The primary aim of this study is to examine the effect of customer experience management (CEM) on brand loyalty in digital retailing. Specifically, the study seeks to assess how personalization, ease of use, and customer support contribute to enhancing customer satisfaction and fostering brand loyalty. The research aims to provide actionable insights for digital retailers on how to optimize these elements to improve customer retention, drive repeat purchases, and strengthen brand loyalty. Research Method: This study employs a quantitative research approach, using a survey method to collect data from 300 respondents who are regular users of digital retail platforms. The survey includes questions designed to measure customer perceptions of personalization, ease of use, and customer support, as well as their overall loyalty to the brand. The data collected is analyzed using statistical techniques to identify correlations between the key factors of customer experience and brand loyalty. The research aims to provide empirical evidence on the significance of these factors in driving customer loyalty in the context of digital retailing. Results and Conclusion: The results of the study reveal that personalization, ease of use, and customer support all play significant roles in enhancing brand loyalty in digital retailing. Personalization, through tailored product recommendations and marketing messages, was found to have a strong positive impact on customers' likelihood to return to digital platforms. Ease of use, including easy navigation and a seamless checkout process, was also found to be crucial in fostering customer satisfaction and loyalty. Furthermore, effective customer support, characterized by quick response times, helpfulness, and the availability of multiple support channels, was identified as a key factor in driving repeat business and building strong customer relationships. The study concludes that businesses that prioritize these elements of customer experience management are more likely to build lasting loyalty and succeed in the competitive digital retail market. Contribution: This study contributes to the existing body of knowledge on customer experience management in digital retailing by providing empirical evidence on the impact of personalization, ease of use, and customer support on brand loyalty. The findings offer valuable insights for digital retailers seeking to enhance their customer experience strategies and improve customer retention. Additionally, the study highlights the importance of integrating these key factors into a cohesive customer experience strategy to foster long-term brand loyalty in the rapidly evolving digital retail environment.